The convection dispersion equation -- not the question, the answer! : anion and cation transport through undisturbed soil columns during unsaturated flow : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Soil Science at Massey University - Vogeler, Iris; Vogeler, Iris (Massey University, 1997)
Prediction of solute movement through the unsaturated zone is important in determining the risk of groundwater contamination from both "natural" and surface applied chemicals. In order to understand better the mechanisms controlling this water-borne transport, unsaturated leaching experiments were carried out on undisturbed soil columns, about 3 litres in volume, for two contrasting soils. One was the weakly-structured Manawatu fine sandy loam, and the other the well-aggregated Ramiha silt loam. Anion transport was satisfactorily described using the convection dispersion equation (CDE), provided that anion exclusion for the Manawatu soil, and adsorption for the Ramiha soil were taken into account. At water flux densities of about 3 mm h-1, a dispersivity of about 40 mm was obtained for the Manawatu soil, and a dispersivity of about 15 mm for the Ramiha soil. The difference was probably due to the contrasting structures of the two soils. Increasing the water flux density in the Manawatu soil to about 13 mm h-1 resulted in a slightly higher dispersivity of about 60 mm. Flow interruption resulted in a subsequent drop in the effluent concentration for the Manawatu soil but not in the Ramiha soil. This suggests that the lag time for transverse molecular diffusion from "mobile" to "immobile" water domains was important in the Manawatu soil, but not in the Ramiha soil. In both soils cation transport was described satisfactorily with the CDE in conjunction with cation exchange theory, providing that only 80% of the cations replaced by 1 M ammonium acetate were assumed to be involved in exchange reactions. Column leaching experiments were also carried out using a rainfall simulator and larger columns of about 22 litres of the Manawatu soil with a short pasture on top. Solid chemical was applied to both a dry and a wet soil surface. Neither the pasture nor the initial water content had a significant effect on solute movement. Slightly higher dispersivities of about 70 mm were found. Time Domain Reflectometry (TDR) was found to be valuable for monitoring solute transport in a repacked soil under transient water flow conditions. But in undisturbed soils TDR only proved to be accurate under steady-state water flow when absolute values of solute concentration were not sought. The CDE was thus found to satisfactorily answer the question of how to describe transport of non-reactive and reactive solutes under bare soil and under short pasture. This applied during both steady-flow and transient wetting.
Keywords: Solute movement; Groundwater; Loam soil; Soil water content; Ground water